Is daycare tonsillectomy a safe outpatient surgery at Pokhara ENT Center, Nepal - Nepali, Rajendra; Dubey, Tulika; K C, Neeraj; Gurung, Banita (Journal of Gandaki Medical College-Nepal, 2022)
Introduction: Tonsillectomy is one of the most common surgical procedure in the world performed by Ear, Nose and Throat surgeon. Over the past decade, there has been progress in surgical techniques for tonsillectomy, yet pain and bleeding after tonsillectomy remain important surgical complications. With the increasing need to reduce healthcare costs in developing countries, there is currently a trend towards performing tonsillectomy on a daycare basis and this study aims at evaluating how efficacious it may be in our setting. Methods: A retrospective review of all the daycare tonsillectomy surgeries performed at the Pokhara ENT Center, Pokhara, Nepal from February 2018 to January 2019. Patients aged 15 years and up of either sex who met the paradise criteria were included while patients who met the same but had a contraindication for tonsillectomy surgery were excluded. Demographic information as well as complications within six hours of surgery before discharge and on follow-up on the seventh post-operative day were evaluated, as were any emergency room visits in the first 24 hours and any complications requiring a visit to a healthcare facility. Results: On day of surgery 17% had worst pain and on seventh post-operative day 75% had no pain, only 2% presented with primary hemorrhage and 3% presented with secondary hemorrhage. None of them required revision surgery. Conclusions: Daycare tonsillectomy is being done in only some of the centers owing to the risk of postoperative complications in our country. In our study, the number of complications was lower and not life-threatening. It can be considered a safe and cost-effective method, though patient selection is crucial.